2016
DOI: 10.1073/pnas.1525665113
|View full text |Cite
|
Sign up to set email alerts
|

Myotubes derived from human-induced pluripotent stem cells mirror in vivo insulin resistance

Abstract: Induced pluripotent stem cells (iPS cells) represent a unique tool for the study of the pathophysiology of human disease, because these cells can be differentiated into multiple cell types in vitro and used to generate patient- and tissue-specific disease models. Given the critical role for skeletal muscle insulin resistance in whole-body glucose metabolism and type 2 diabetes, we have created a novel cellular model of human muscle insulin resistance by differentiating iPS cells from individuals with mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…This "convergence" may possibly be linked to epigenetic alterations that occur upon iPSC reprogramming. Although it has been previously shown that iPSCs and iPSC-derived cells from patients with genetic insulinresistance model in vivo defects observed in patients with type 2 diabetes (53,54), it is known that epigenetic mechanisms occurring during reprogramming can remove epigenetic marks associated with disease phenotypes (55). Our findings are supported by recent studies showing a similar "phenotypic convergence" in iPSC-derived dopaminergic neurons reprogrammed from sporadic Parkinson's disease (56) and iPSC-derived fibroblasts reprogrammed from scleroderma (57).…”
Section: Discussionsupporting
confidence: 85%
“…This "convergence" may possibly be linked to epigenetic alterations that occur upon iPSC reprogramming. Although it has been previously shown that iPSCs and iPSC-derived cells from patients with genetic insulinresistance model in vivo defects observed in patients with type 2 diabetes (53,54), it is known that epigenetic mechanisms occurring during reprogramming can remove epigenetic marks associated with disease phenotypes (55). Our findings are supported by recent studies showing a similar "phenotypic convergence" in iPSC-derived dopaminergic neurons reprogrammed from sporadic Parkinson's disease (56) and iPSC-derived fibroblasts reprogrammed from scleroderma (57).…”
Section: Discussionsupporting
confidence: 85%
“…Human immortalized LHCN-M2 myoblast differentiation to myotubes was accompanied by increased troponin T expression (33), while a-actinin protein, which increases with Z-line formation but not before, was unchanged (40), both as expected. The myotubes were responsive to insulin, a characteristic of skeletal muscle (41). GLUT4 increased with differentiation while GLUT1 decreased, consistent with previous data (42).…”
Section: Discussionsupporting
confidence: 91%
“…These cultures have the potential to model insulin resistance in 3D but have only been studied in 2D. Iovino et al generated myotubes from healthy volunteers and individuals with Donohue syndrome, a genetic disorder associated with mutations in the insulin receptor [78]. The myotubes derived from individuals with Donohue syndrome exhibited defects in insulin signalling, glucose uptake and glycogen accumulation, as well as insulin-regulated gene expression.…”
Section: Don't Believe the Hype: Organoid Limitationsmentioning
confidence: 99%